TRANSFORMASI MANAJEMEN SUMBER DAYA MANUSIA DI ERA DIGITAL: LITERATURE REVIEW - Ades Asike; Arfandy Dinsar; Ulyana Muslimin (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The digital transformation of Human Resource Management (HRM) has become a strategic issue in response to rapid technological advancements and changing organizational environments. This study aims to systematically examine the development, key themes, and challenges of digital HRM transformation through a systematic literature review (SLR). Literature was collected from reputable academic databases, including Scopus, Web of Science, ScienceDirect, and Google Scholar, covering publications from 2015 to 2024. The findings indicate that HRM transformation encompasses the digitalization of HR processes, the adoption of artificial intelligence and HR analytics, the strategic repositioning of the HR function, and changes in employee experience and work patterns. Nevertheless, the literature also highlights critical challenges related to ethical concerns, algorithmic bias, data privacy, and digital capability readiness. This study concludes that digital HRM transformation represents a complex and ongoing socio-technical process that requires the integration of technology, human capabilities, and organizational strategy. The findings are expected to contribute to the advancement of digital HRM literature and provide conceptual insights for managerial practice and future research.